X-rays can trigger the FLASH effect: Ultra-high dose-rate synchrotron light source prevents normal brain injury after whole brain irradiation in mice. Issue 3 (December 2018) - Montay-Gruel, Pierre; Bouchet, Audrey; Jaccard, Maud; Patin, David; Serduc, Raphael; Aim, Warren; Petersson, Kristoffer; Petit, Benoit; Bailat, Claude; Bourhis, Jean; Bräuer-Krisch, Elke; Vozenin, Marie-Catherine
Abstract: This study is the first proof of concept that the FLASH effect can be triggered by X-rays. Our results show that a 10 Gy whole-brain irradiation delivered at ultra-high dose-rate with synchrotron generated X-rays does not induce memory deficit; it reduces hippocampal cell-division impairment and induces less reactive astrogliosis.